The foray of "Hallyu" as a promoter of South Korean culture in Asian World magazine, Peru, 2019-2020. - Cruz Romero, Jasmin Lisbeth (2022)
The article analyzes the promotion of South Korean popular culture, known as Hallyu, in the Peruvian magazine Asian World from its journalistic treatment during the years 2019 - 2020. The study aimed to identify in news terms the main elements of this phenomenon of expansion of pop music, soap operas and fan club events, thanks to the Internet and social networks. To do so, it covered eight editions of the publication on the characteristics of the cover, special section and doramas section. It is concluded that the dissemination of news about K-pop and doramas encourages Hallyu in Peru, as explained by McLuhan (1971) when referring to the global village that describes the immediacy of information through globalization and the internet, which allow its propagation throughout the planet in a dynamic, permanent and current way.